23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686

3 Tesla (23)Na Magnetic Resonance Imaging During Acute Kidney Injury - Hammon, Matthias; Großmann, Susan; Linz, Peter; Seuss, Hannes; Hammon, Rebecca; Rosenhauer, Daniela; Janka, Rolf Matthias; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Dahlmann, Anke; Cavallaro, Alexander Josef (Academic Radiology, 2017)
Sodium and proton magnetic resonance imaging ((23)Na/(1)H-MRI) have shown that muscle and skin can store Na(+) without water. In chronic renal failure and in heart failure, Na(+) mobilization occurs, but is variable depending on age, dialysis vintage, and other features. Na(+) storage depots have not been studied in patients with acute kidney injury (AKI).We studied 7 patients with AKI (mean age: 51.7 years; range: 25-84) and 14 age-matched and gender-matched healthy controls. All underwent (23)Na/(1)H-MRI at the calf. Patients were studied before and after acute hemodialysis therapy within 5-6 days. The (23)Na-MRI produced grayscale images containing Na(+) phantoms, which served to quantify Na(+) contents. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na(+) levels did not change. Mean Na(+) contents in muscle and skin did not significantly change following four to five cycles of hemodialysis treatment (before therapy: 32.7 ± 6.9 and 44.2 ± 13.5 mmol/L, respectively; after dialysis: 31.7 ± 10.2 and 42.8 ± 11.8 mmol/L, respectively; P > .05). Water content measurements did not differ significantly before and after hemodialysis in muscle and skin (P > .05). Na(+) contents in calf muscle and skin of patients before hemodialysis were significantly higher than in healthy subjects (16.6 ± 2.1 and 17.9 ± 3.2) and remained significantly elevated after hemodialysis.Na(+) in muscle and skin accumulates in patients with AKI and, in contrast to patients receiving chronic hemodialysis and those with acute heart failure, is not mobilized with hemodialysis within 5-6 days.
EVALuna2:14621

3 Tesla (23)Na magnetic resonance imaging during aerobic and anaerobic exercise - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Janka, Rolf Matthias; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (Academic Radiology, 2015)
The aim of the work described here was to determine the feasibility of monitoring Na(+) concentration and distribution in muscle/skin during aerobic/anaerobic exercise with (23)Na magnetic resonance imaging (MRI).The Na(+) concentration and water content of muscle/skin of the left lower leg of six healthy subjects (mean age, 26 years; range, 22-30 years; three men and three women) were assessed before and after aerobic/anaerobic cycle ergometry and during recovery with 3-T (23)Na/(1)H MRI. (23)Na MRI was performed with a custom-made knee coil. A gradient echo sequence with an acquisition time of 3.25 minutes, echo time of 2.07 ms, repetition time of 100 ms, and spatial resolution of 3 × 3 × 30 mm(3) was applied. Phantoms with increasing sodium concentration served for quantification via linear extrapolation. Blood values were determined by blood gas analysis.The concentration of Na(+) significantly increased during anaerobic exercise in all muscle compartments except the medial gastrocnemius muscle, whereas no significant change was observed in most muscle compartments during aerobic exercise (only the soleus muscle exhibited a significant increase in Na(+) concentration during aerobic exercise: 1.6 ± 1.5 mmol/kg, 4.5%, P = .046). During anaerobic exercise, the mean Na(+) concentration of the triceps surae and the whole leg increased by 9.0% (3.1 ± 2.1 mmol/kg, P = .016) and 6.5% (2.2 ± 1.3 mmol/kg, P < .01). MRI revealed a water-independent increase in Na(+) concentration in most muscle compartments during anaerobic exercise. Na(+) concentration significantly decreased during recovery after anaerobic and aerobic exercise in all muscle compartments except the soleus. The Na(+) concentration of the skin did not significantly change during anaerobic/aerobic exercise.Sodium(23) MRI allows reliable and noninvasive visualization and quantification of Na(+) concentration and distribution in muscle and skin during exercise. (23)Na MRI can be used to gain new insights into Na(+) homeostasis, presumably leading to better comprehension of pathophysiology.
EVALuna2:3827

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

Cardiac Phenotype and Tissue Sodium Content in Adolescents with Defects in the Melanocortin System - Puder, Lia; Roth, Sophie; Krabusch, Philipp; Wiegand, Susanna; Opitz, Robert; Bald, Martin; Flück, Christa; Schulz, Esther; Voss, Egbert; Markó, Lajos; Linz, Peter; Berger, Felix; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: Pro-opiomelanocortin (POMC) and the melanocortin-4 receptor (MC4R) play a pivotal role in the leptin-melanocortin pathway. Mutations in these genes lead to monogenic types of obesity due to severe hyperphagia. In addition to dietary-induced obesity, a cardiac phenotype without hypertrophy has been identified in MC4R knockout mice. Objective: We aimed to characterize cardiac morphology and function as well as tissue Na+ content in humans with mutations in POMC and MC4R genes. Methods: A cohort of 42 patients (5 patients with bi-allelic POMC mutations, 6 heterozygous MC4R mutation carriers, 19 obese controls without known monogenic cause, and 12 normal weight controls) underwent cardiac magnetic resonance (CMR) imaging and 23Na-MRI. Results: Monogenic obese patients with POMC or MC4R mutation respectively had a significantly lower left ventricular mass/body surface area (BSA) than nonmonogenic obese patients. Left ventricular end-diastolic volume/BSA was significantly lower in POMC-and MC4R-deficient patients than in nonmonogenic obese patients. Subcutaneous fat and skin Na+ content was significantly higher in POMC-and MC4R-deficient patients than in nonmonogenic obese patients. In these compartments, the water content was significantly higher in patients with POMC and MC4R mutation than in control groups. Conclusion: Patients with POMC or MC4R mutations carriers had a lack of transition to hypertrophy, significantly lower cardiac muscle mass/BSA, and stored more Na+ within the subcutaneous fat tissue than nonmonogenic obese patients. The results point towards the role of the melanocortin pathway for cardiac function and tissue Na+ storage and the importance of including cardiologic assessments into the diagnostic work-up of these patients.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiac function; left ventricular function; MC4R; melanocortin pathway; Monogenic obesity; POMC; tissue sodium content; tissue water content

Combined imaging of potassium and sodium in human skeletal muscle tissue at 7 T - Gast, Lena; Volker, Stefanie; Utzschneider, Matthias; Linz, Peter; Wilferth, Tobias; Müller, Max; Kopp, Christoph; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2020)
Purpose: To validate the feasibility of quantitative combined potassium (39K) and sodium (23Na) MRI in human calf muscle tissue, as well as to evaluate the reproducibility of the apparent tissue potassium concentration (aTPC) and apparent tissue sodium concentration (aTSC) determination in healthy muscle tissue. Methods: Quantitative 23Na and 39K MRI acquisition protocols were implemented on a 7 T MR system. A double-resonant 23Na/39K birdcage RF coil was used. Measurements of human lower leg were performed in a total acquisition time of TANa = 10:54 min/TAK = 8:06 min and using a nominal spatial resolution of 2.5 × 2.5 × 15 mm3/7.5 × 7.5 × 30 mm3 for 23Na/39K MRI. Two aTSC and aTPC examinations in muscle tissue were performed during the same day on 10 healthy subjects. Results: The proposed acquisition and postprocessing workflow for 23Na and 39K MRI data sets provided reproducible aTSC and aTPC measurements. In human calf muscle tissue, the coefficient of variation between scan and re-scan was 5.7% for both aTSC and aTPC determination. Overall, mean values of aTSC = (17 ± 1) mM and aTPC = (85 ± 5) mM were measured. Moreover, for 39K in calf muscle tissue, (Formula presented.) components of (Formula presented.) = (1.2 ± 0.2) ms and (Formula presented.) = (7.9 ± 0.9) ms, as well as a residual quadrupolar interaction of (Formula presented.) = (143 ± 17) Hz, were determined. The fraction of the fast component was f = (58 ± 4)%. Conclusion: Using the presented measurement and postprocessing approach, a reproducible aTSC and aTPC determination using 23Na and 39K MRI at 7 T in human skeletal muscle tissue is feasible in clinically acceptable acquisition durations.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7 T; potassium MRI; sodium MRI; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Correction: Muscle sodium content in patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (Journal of Translational Medicine, (2022), 20, 1, (580), 10.1186/s12967-022-03616-z) - Petter, Elisabeth; Scheibenbogen, Carmen; Linz, Peter; Stehning, Christian; Wirth, Klaus; Kuehne, Titus; Kelm, Marcus (Journal of Translational Medicine, 2023)
CRIS-Team Scopus Importer:2023-04-28

Effect Of Sunitinib Treatment On Skin Sodium Accumulation In Patients With Metastatic Renal Cancer: A Pilot Study - Marko, Lajos; Dorr, Anne; Linz, Peter; Van Den Meiracker, H. Anton; Kuhne, Titus; Dechend, Ralf; Danser, Jan H.; Florcken, Anne; Mueller, Dominik N. (HYPERTENSION, 2020)
CRIS-Team WoS Importer:2021-03-05

Effect of Sunitinib Treatment on Skin Sodium Accumulation in Patients With Renal Cancer: a Pilot Study - Marko, Lajos; Dorr, Anne; Linz, Peter; Van Den Meiracker, Anton H.; Garrelds, Ingrid M.; Kuehne, Titus; Dechend, Ralf; Danser, A. H. Jan; Floercken, Anne; Mueller, Dominik N. (Hypertension, 2022)
CRIS-Team Scopus Importer:2022-04-29
Keywords: blood pressure; homeostasis; hypertension; skin; sodium; sunitinib; vascular endothelial growth factor c

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Elevated tissue sodium deposition in patients with type 2 diabetes on hemodialysis detected by 23Na magnetic resonance imaging - Kopp, Christoph; Linz, Peter; Maier, Carolin; Wabel, Peter; Hammon, Matthias; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Uder, Michael; Luft, Friedrich C.; Titze, Jens; Dahlmann, Anke (Kidney International, 2018)
Long-term elevated blood sugar levels result in tissue matrix compositional changes in patients with diabetes mellitus type 2 (T2DM). We hypothesized that hemodialysis patients with T2DM might accumulate more tissue sodium than control hemodialysis patients. To test this, 23Na magnetic resonance imaging (23Na MRI) was used to estimate sodium in skin and muscle tissue in hemodialysis patients with or without T2DM. Muscle fat content was estimated by 1H MRI and tissue sodium content by 23Na MRI pre- and post-hemodialysis in ten hemodialysis patients with T2DM and in 30 matched control hemodialysis patients. We also assessed body fluid distribution with the Body Composition Monitor. 1H MRI indicated a tendency to higher muscle fat content in hemodialysis patients with T2DM compared to non-diabetic hemodialysis patients. 23Na MRI indicated increased sodium content in muscle and skin tissue of hemodialysis patients with T2DM compared to control hemodialysis patients. Multi-frequency bioimpedance was used to estimate extracellular water (ECW), and excess ECW in T2DM hemodialysis patients correlated with HbA1c levels. Sodium mobilization during hemodialysis lowered muscle sodium content post-dialysis to a greater degree in T2DM hemodialysis patients than in control hemodialysis patients. Thus, our findings provide evidence that increased sodium accumulation occurs in hemodialysis patients with T2DM and that impaired serum glucose metabolism is associated with disturbances in tissue sodium and water content.
EVALuna2:34700

Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Friedrich, Anna Carolina; Linz, Peter; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Schiffer, Mario; Uder, Michael; Kopp, Christoph; Dahlmann, Anke (Kidney & Blood Pressure Research, 2022)
BACKGROUND: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. METHODS: In our observational study, 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-magnetic resonance imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by bioimpedance spectroscopy (BIS) and laboratory parameters were assessed. RESULTS: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units (a.u.), p < 0.01) and muscle tissue (21.5 ± 3.6 vs. 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, includingexcess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/mL, p < 0.05). CONCLUSION: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 23Na-magnetic resonance imaging; Cardiovascular disease; Hemodialysis; Tissue Na+

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI - Mennecke, Angelika; Nagel, Armin Michael; Huhn, Konstantin; Linker, Ralf; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2021)
Background Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type Prospective. Subjects Twenty-nine relapsing-remitting MS patients with an acute relapse were included. Field Strength/Sequence A 3D density-adapted radial sodium sequence at 3 T using a dual-tuned (Na-23/H-1) head coil. Assessment Full-brain images of the tissue sodium concentration (TSC1, n = 29) and a sodium inversion recovery sequence (SIR1, n = 20) at the beginning of the anti-inflammatory therapy and on medium-term follow-up visits (days 27-99, n = 12 [TSC], n = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1CE+) and without change in T1-weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests nTSC and nSIR were compared regarding the type of lesion and the time point using a one-way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1-nTSC2 over nSIR1. A P-value At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T(1)n and the T1CE+ lesions in comparison to the normal-appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level 2 Technical Efficacy Stage 4
CRIS-Team WoS Importer:2021-07-23

Magnetic resonance-determined sodium removal from tissue stores in hemodialysis patients - Dahlmann, Anke; Dörfelt, Kathrin; Eicher, Florian; Linz, Peter; Kopp, Christoph; Mössinger, Irina; Horn, Stephan; Bueschges-Seraphin, Beatrix; Wabel, Peter; Hammon, Matthias; Eckardt, Kai-Uwe; Kotanko, Peter; et al. (Kidney International, 2015)
We have previously reported that sodium is stored in skin and muscle. The amounts stored in hemodialysis (HD) patients are unknown. We determined whether (23)Na magnetic resonance imaging (sodium-MRI) allows assessment of tissue sodium and its removal in 24 HD patients and 27 age-matched healthy controls. We also studied 20 HD patients before and shortly after HD with a batch dialysis system with direct measurement of sodium in dialysate and ultrafiltrate. Age was associated with higher tissue sodium content in controls. This increase was paralleled by an age-dependent decrease of circulating levels of vascular endothelial growth factor-C (VEGF-C). Older (>60 years) HD patients showed increased sodium and water in skin and muscle and lower VEGF-C levels compared with age-matched controls. After HD, patients with low VEGF-C levels had significantly higher skin sodium content compared with patients with high VEGF-C levels (low VEGF-C: 2.3 ng/ml and skin sodium: 24.3 mmol/l; high VEGF-C: 4.1 ng/ml and skin sodium: 18.2 mmol/l). Thus, sodium-MRI quantitatively detects sodium stored in skin and muscle in humans and allows studying sodium storage reduction in ESRD patients. Age and VEGF-C-related local tissue-specific clearance mechanisms may determine the efficacy of tissue sodium removal with HD. Prospective trials on the relationship between tissue sodium content and hard end points could provide new insights into sodium homeostasis, and clarify whether increased sodium storage is a cardiovascular risk factor.
EVALuna2:3717

Modification of Dialysate Na+ Concentration but not Ultrafiltration or Dialysis Treatment Time Affects Tissue Na+ Deposition in Patients on Hemodialysis. - Kopp, Christoph; Kittler, Lukas; Linz, Peter; Kannenkeril, Dennis; Horn, Stephan; Chazot, Charles; Schiffer, Mario; Uder, Michael; Nagel, Armin Michael; Dahlmann, Anke (Kidney International Reports, 2024)
INTRODUCTION: Tissue Na+ overload is present in patients receiving hemodialysis (HD) and is associated with cardiovascular mortality. Strategies to actively modify tissue Na+ amount in these patients by adjusting the HD regimen have not been evaluated. METHODS: In several substudies, including cross-sectional analyses (n = 75 patients on HD), a cohort study and a cross-over interventional study (n = 10 patients each), we assessed the impact of ultrafiltration (UF) volume, prolongation of dialysis treatment time, and modification of dialysate Na+ concentration on tissue Na+ content using 23Na magnetic resonance imaging (23Na-MRI). RESULTS: In the cross-sectional analysis of our patients on HD, differences in dialysate sodium concentration ([Na+]) were associated with changes in tissue Na+ content, whereas neither UF volume nor HD treatment time affected tissue Na+ amount. Skin Na+ content was lower in 17 patients on HD, with dialysate [Na+] of <138 mmol/l compared to 58 patients dialyzing at ≥138 mmol/l (20.7 ± 7.3 vs. 26.0 ± 8.8 arbitrary units [a.u.], P < 0.05). In the cohort study, intraindividual prolongation of HD treatment time was not associated with a reduction in tissue Na+ content. Corresponding to the observational data, intraindividual modification of dialysate [Na+] from 138 to 142 to 135 mmol/l resulted in concordant changes in skin Na+ (24.3 ± 7.6 vs. 26.3 ± 8.0 vs. 20.8 ± 5.6 a.u, P < 0.05 each), whereas no significant change in muscle Na+ occurred. CONCLUSION: Solely adjustment of dialysate [Na+] had a reproducible impact on tissue Na+ content. 23Na-MRI could be utilized to monitor the effectiveness of dialysate [Na+] modifications in randomized-controlled outcome trials.
EVALuna2:568181

Multiple interleaved mode saturation (MIMOSA) for B1+ inhomogeneity mitigation in chemical exchange saturation transfer - Liebert, Andrzej; Gumbrecht, Rene; Tkotz, Katharina; Linz, Peter; Schmitt, Benjamin; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael; Zaiss, Moritz; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2019)
Purpose: To mitigate (Formula presented.) inhomogeneity in quantitative CEST MRI at ultra-high magnetic field strengths (B 0 ≥ 7 Tesla) using a parallel transmit system. Methods: Multiple interleaved mode saturation employs interleaving of 2 complementary phase sets during the saturation pulse train. Phase differences of 45° (first mode) and 90° (second mode) between 2 adjacent transmitter coil channels are used. The influence of the new saturation scheme on the CEST contrast was analyzed using Bloch-McConnell simulations. The presented method was verified in phantom and in vivo measurements of the healthy human brain. The relayed nuclear Overhauser effect was evaluated, and the inverse magnetic transfer ratio metric was calculated. Results were compared to a published (Formula presented.) correction method. All measurements were conducted on a whole-body 7 Tesla MRI system using an 8 transmitter and 32 receiver channel head coil. Results: Simulations showed that the inverse magnetic transfer ratio metric contrast of relayed nuclear Overhauser effect shows a smaller dependency on the relative amplitudes of the 2 different modes than the contrasts of Cr and amide proton transfer. Measurements of an egg white phantom showed markedly improved homogeneity compared to the uncorrected inverse magnetic transfer ratio metric (relayed nuclear Overhauser effect) images and slightly improved results compared to (Formula presented.) corrected images. In vivo multiple interleaved mode saturation images showed similar contrast compared to (Formula presented.) corrected images. Conclusion: Multiple interleaved mode saturation can be used as a simple method to mitigate (Formula presented.) inhomogeneity effects in CEST MRI at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced because an additional scan, usually required for (Formula presented.) correction, can be omitted.
CRIS-Team Scopus Importer:2019-05-02
Keywords: 7 Tesla; B1 shimming; chemical exchange saturation transfer; parallel transmission (pTx); pulsed CEST; RF inhomogeneity; ultra-high-field MRI

Muscle sodium content in patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Petter, Elisabeth; Scheibenbogen, Carmen; Linz, Peter; Stehning, Christian; Wirth, Klaus; Kuehne, Titus; Kelm, Marcus (Journal of Translational Medicine, 2022)
Background: Muscle fatigue and pain are key symptoms of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). Although the pathophysiology is not yet fully understood, there is ample evidence for hypoperfusion which may result in electrolyte imbalance and sodium overload in muscles. Therefore, the aim of this study was to assess levels of sodium content in muscles of patients with ME/CFS and to compare these to healthy controls. Methods: Six female patients with ME/CFS and six age, BMI and sex matched controls underwent 23Na-MRI of the left lower leg using a clinical 3T MR scanner before and after 3 min of plantar flexion exercise. Sodium reference phantoms with solutions of 10, 20, 30 and 40 mmol/L NaCl were used for quantification. Muscle sodium content over 40 min was measured using a dedicated plugin in the open-source DICOM viewer Horos. Handgrip strength was measured and correlated with sodium content. Results: Baseline tissue sodium content was higher in all 5 lower leg muscle compartments in ME/CFS compared to controls. Within the anterior extensor muscle compartment, the highest difference in baseline muscle sodium content between ME/CFS and controls was found (mean ± SD; 12.20 ± 1.66 mM in ME/CFS versus 9.38 ± 0.71 mM in controls, p = 0.0034). Directly after exercise, tissue sodium content increased in gastrocnemius and triceps surae muscles with + 30% in ME/CFS (p = 0.0005) and + 24% in controls (p = 0.0007) in the medial gastrocnemius muscle but not in the extensor muscles which were not exercised. Compared to baseline, the increase of sodium content in medial gastrocnemius muscle was stronger in ME/CFS than in controls with + 30% versus + 17% to baseline at 12 min (p = 0.0326) and + 29% versus + 16% to baseline at 15 min (p = 0.0265). Patients had reduced average handgrip strength which was associated with increased average muscle tissue sodium content (p = 0.0319, R2 = 0.3832). Conclusion: Muscle sodium content before and after exercise was higher in ME/CFS than in healthy controls. Furthermore, our findings indicate an inverse correlation between muscle sodium content and handgrip strength. These findings provide evidence that sodium overload may play a role in the pathophysiology of ME/CFS and may allow for potential therapeutic targeting.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Chronic Fatigue Syndrome; Exercise; Magnetic Resonance Imaging; Muscle; skeletal; Myalgia; Sodium; Sodium–hydrogen exchangers; Sodium–potassium-exchanging ATPase

Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure, the control of renal sympathetic nerve activity (RSNA) by the cardio-renal baroreflex was impaired. The afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than that in controls. Hence, by investigating respective first neurons in the nodose ganglion (NG), we wanted to test the hypothesis that after myocardial infarction with still-preserved ejection fraction, the cardiac afferent nerve pathway is also already impaired. Material and methods: A myocardial infarction was induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. A current clamp was used to characterize neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., <5 APs upon current injection. Cardiac ejection fraction was measured using echocardiography; RSNA was recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology was studied for inflammation and fibrosis markers. Results: A total of 192 neurons were investigated. In rats, after myocardial infarction, the number of neurons with a tonic response pattern increased compared to that in the controls (infarction vs. control: 78.6% vs. 48.5%; z-test, *p < 0.05), with augmented production of APs (23.7 ± 2.86 vs. 15.5 ± 1.86 APs/600 ms; mean ± SEM, t-test, *p < 0.05). The baseline activity of RSNA was subtly increased, and its control by the cardiopulmonary baroreflex was impaired following myocardial infarction: the fibrosis marker collagen I augmented in the renal interstitium. Discussion: After myocardial infarction with still-preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac afferent neurons after myocardial infarction cardiac afferent innervation; congestive heart failure; myocardial infarction; neuronal cell culture; preserved ejection fraction; renal innervation

Na-23-MRI reveals sodium accumulation in skin of patients with relapsing-remitting multiple sclerosis - Huhn, K.; Linz, Peter; Pemsel, F.; Waschbisch, Anne; Lee, De-Hyung; Kopp, C.; Uder, Michael; Titze, J.; Mueller, D. N.; Linker, Ralf (2015)
EVALuna2:14485

Na+ deposition in the fibrotic skin of systemic sclerosis patients detected by 23Na-magnetic resonance imaging - Kopp, Christoph; Beyer, Christian; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Neubert, Patrick; Rosenhauer, Daniela; Mueller, Dominik N.; Eckardt, Kai-Uwe; Schett, Georg; Luft, Friedrich C.; et al. (Rheumatology, 2017)
Skin fibrosis is the predominant feature of SSc and arises from excessive extracellular matrix deposition. Glycosaminoglycans are macromolecules of the extracellular matrix, which facilitate Na(+) accumulation in the skin. We used (23)Na-MRI to quantify Na(+) in skin. We hypothesized that skin Na(+) might accumulate in SSc and might be a biomarker for skin fibrosis.In this observational case-control study, skin Na(+) was determined by (23)Na-MRI using a Na(+) volume coil in 12 patients with diffuse cutaneous SSc and in 21 control subjects. We assessed skin fibrosis by the modified Rodnan skin score prior to (23)Na-MRI and on follow-up 12 months later.(23)Na-MRI demonstrated increased Na(+) in the fibrotic skin of SSc patients compared with skin from controls [mean (sd): 27.2 (5.6) vs 21.4 (5.3) mmol/l, P < 0.01]. Na(+) content was higher in fibrotic than in non-fibrotic SSc skin [26.2 (4.8) vs 19.2 (3.4) mmol/l, P < 0.01]. Furthermore, skin Na(+) amount was correlated with changes in follow-up modified Rodnan skin score (R(2) = 0.68).(23)Na-MRI detected increased Na(+) in the fibrotic SSc skin; high Na(+) content was associated with progressive skin disease. Our findings provide the first evidence that (23)Na-MRI might be a promising tool to assess skin Na(+) and thereby predict progression of skin fibrosis in SSc.
EVALuna:33997

NCX1 represents an ionic Na+ sensing mechanism in macrophages - Neubert, Patrick; Homann, Arne; Wendelborn, David; Bär, Anna Lorena; Krampert, Luka; Trum, Maximilian; Schröder, Agnes; Ebner, Stefan; Weichselbaum, Andrea; Schatz, Valentin; Linz, Peter; Veelken, Roland; et al. (Plos Biology, 2020)
Inflammation and infection can trigger local tissue Na+ accumulation. This Na+-rich environment boosts proinflammatory activation of monocyte/macrophage-like cells (MΦs) and their antimicrobial activity. Enhanced Na+-driven MΦ function requires the osmoprotective transcription factor nuclear factor of activated T cells 5 (NFAT5), which augments nitric oxide (NO) production and contributes to increased autophagy. However, the mechanism of Na+ sensing in MΦs remained unclear. High extracellular Na+ levels (high salt [HS]) trigger a substantial Na+ influx and Ca2+ loss. Here, we show that the Na+/Ca2+ exchanger 1 (NCX1, also known as solute carrier family 8 member A1 [SLC8A1]) plays a critical role in HS-triggered Na+ influx, concomitant Ca2+ efflux, and subsequent augmented NFAT5 accumulation. Moreover, interfering with NCX1 activity impairs HS-boosted inflammatory signaling, infection-triggered autolysosome formation, and subsequent antibacterial activity. Taken together, this demonstrates that NCX1 is able to sense Na+ and is required for amplifying inflammatory and antimicrobial MΦ responses upon HS exposure. Manipulating NCX1 offers a new strategy to regulate MΦ function.
CRIS-Team Scopus Importer:2020-07-03

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

OS 12-03 SGLT-2-INHIBITION WITH DAPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT - Schmieder, Roland; Ott, Christian; Linz, Peter; Jumar, Agnes; Friedrich, Stefanie; Titze, Jens; Hammon, Matthias; Uder, Michael; Kistner, Iris (Journal of Hypertension, 2016)
Sodium tissue content by Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and, in parallel, of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes leads to decreased tissue sodium content due to its pharmacological action.In a prospective, double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to dapagliflozin 10 mg o.d. and placebo for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analyzed the sodium content in the skin and muscles of the lower leg by the Na-MRI at baseline, after the first and second treatment phase of 6 weeks.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11, p = 0.010) and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024) 24-hour ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline (24.1 ± 6.6 vs.22.7 ± 6.4 mmol/L; p = 0.013). No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 mmol/L, p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in sodium tissue content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes known to be salt sensitive and prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition.
EVALuna2:14604

Quantitative assessment of muscle injury by (23)Na magnetic resonance imaging - Dahlmann, Anke; Kopp, Christoph; Linz, Peter; Seuß, Hannes; Eckardt, Kai-Uwe; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (SpringerPlus, 2016)
(23)Na magnetic resonance imaging ((23)Na-MRI) is able to measure Na(+) in vivo in humans and allows quantification of tissue sodium distribution. We now tested the utility of (23)Na-MRI technique in detecting and assessing sports-related acute muscular injury.We assessed tissue Na(+) of both lower legs with a 3T MRI scanner using a customized (23)Na knee coil. The affected left calf muscle in an injured volleyball player showed a hyperintense Na(+) signal. Follow-up measurements revealed persistently increased muscle Na(+) content despite complete clinical recovery.Our findings suggest that (23)Na-MRI could have utility in detecting subtle muscular injury and might indicate when complete healing has occurred. Furthermore, (23)Na-MRI suggests the presence of substantial injury-related muscle electrolyte shifts that warrant more detailed investigation.
EVALuna2:3865

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Reduction of tissue sodium content by SGLT-2-inhibition with dapagliflozin - Karg, M. V.; Ott, Christian; Linz, Peter; Jumar, A.; Kannenkeril, Dennis; Titze, J.; Hammon, Matthias; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36268

Reliability and agreement of sodium (23Na) MRI in calf muscle and skin of healthy subjects from the US - Dyke, Jonathan P.; Meyring-Wosten, Anna; Zhao, Yize; Linz, Peter; Thijssen, Stephan; Kotanko, Peter (Clinical Imaging, 2018)
PURPOSE: To quantify the reliability and agreement of sodium (23Na) MRI in calf muscle and skin of healthy subjects and to measure the smallest real difference (SRD) in each. SUBJECTS AND METHODS: Thirty healthy subjects underwent 23Na MRI studies of the calf. A scan-rescan protocol was performed the same day and 1 week later. Relative sodium concentration was measured in the calf muscle and skin and compared between studies. RESULTS: A high degree of reliability was confirmed between the scan and rescan tests using linear regression analysis. The Bland-Altman plots indicated high agreement between runs in all regions. The SRD was measured between scans taken the same day and one week later. Correlations were also reported with age, gender and race. CONCLUSIONS: Reliability and agreement of 23Na MRI in the calf muscle and skin show promise for accurately assessing serial changes in patients.
EVALuna2:212702

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, Dennis; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Skin Sodium Accumulates in Psoriasis and Reflects Disease Severity - Maifeld, András; Wild, Johannes; Karlsen, Tine V.; Rakova, Natalia; Wistorf, Elisa; Linz, Peter; Jung, Rebecca; Birukov, Anna; Gimenez-Rivera, Vladimir Andrey; Wilck, Nicola; Bartolomaeus, Theda; Dechend, Ralf; et al. (Journal of Investigative Dermatology, 2021)
Sodium can accumulate in the skin at concentrations exceeding serum levels. A high sodium environment can lead to pathogenic T helper 17 cell expansion. Psoriasis is a chronic inflammatory skin disease in which IL-17‒producing T helper 17 cells play a crucial role. In an observational study, we measured skin sodium content in patients with psoriasis and in age-matched healthy controls by Sodium-23 magnetic resonance imaging. Patients with PASI > 5 showed significantly higher sodium and water content in the skin but not in other tissues than those with lower PASI or healthy controls. Skin sodium concentrations measured by Sodium-23 spectroscopy or by atomic absorption spectrometry in ashed-skin biopsies verified the findings with Sodium-23 magnetic resonance imaging. In vitro T helper 17 cell differentiation of naive CD4+ cells from patients with psoriasis markedly induced IL-17A expression under increased sodium chloride concentrations. The imiquimod-induced psoriasis mouse model replicated the human findings. Extracellular tracer Chromium-51–EDTA measurements in imiquimod- and sham-treated skin showed similar extracellular volumes, rendering excessive water of intracellular origin. Chronic genetic IL-17A‒driven psoriasis mouse models underlined the role of IL-17A in dermal sodium accumulation and inflammation. Our data describe skin sodium as a pathophysiological feature of psoriasis, which could open new avenues for its treatment.
CRIS-Team Scopus Importer:2021-08-13

Skin Sodium Concentration Correlates with Left Ventricular Hypertrophy in CKD - Schneider, Markus P.; Raff, Ulrike; Kopp, Christoph; Scheppach, Johannes B.; Toncar, Sebastian; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Floege, Juergen; Schmid, Matthias; Birukov, Anna; Dahlmann, Anke; et al. (Journal of the American Society of Nephrology, 2017)
The pathogenesis of left ventricular hypertrophy in patients with CKD is incompletely understood. Sodium intake, which is usually assessed by measuring urinary sodium excretion, has been inconsistently linked with left ventricular hypertrophy. However, tissues such as skin and muscle may store sodium. Using (23)sodium-magnetic resonance imaging, a technique recently developed for the assessment of tissue sodium content in humans, we determined skin sodium content at the level of the calf in 99 patients with mild to moderate CKD (42 women; median [range] age, 65 [23-78] years). We also assessed total body overhydration (bioimpedance spectroscopy), 24-hour BP, and left ventricular mass (cardiac magnetic resonance imaging). Skin sodium content, but not total body overhydration, correlated with systolic BP (r=0.33, P=0.002). Moreover, skin sodium content correlated more strongly than total body overhydration did with left ventricular mass (r=0.56, P<0.001 versus r=0.35, P<0.001; P<0.01 between the two correlations). Linear regression analysis demonstrated that skin sodium content is a strong explanatory variable for left ventricular mass, unaffected by BP and total body overhydration. In conclusion, we found skin sodium content to be closely linked to left ventricular mass in patients with CKD. Interventions that reduce skin sodium content might improve cardiovascular outcomes in these patients.
EVALuna2:3863

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium

Skin sodium is increased in male patients with multiple sclerosis and related animal models - Huhn, Konstantin; Linz, Peter; Pemsel, Franziska; Michalke, Bernhard; Seyferth, Stefan; Kopp, Christoph; Chaudri, Mohammad Anwar; Rothhammer, Veit; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.; Müller, Dominik N.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Novel MRI techniques allow a noninvasive quantification of tissue sodium and reveal the skin as a prominent compartment of sodium storage in health and disease. Since multiple sclerosis (MS) immunopathology is initiated in the periphery and increased sodium concentrations induce proinflammatory immune cells, the skin represents a promising compartment linking high sodium concentrations and MS immunopathology. We used a 7-T sodium MRI (23Na-MRI) and inductively coupled plasma mass spectrometry to investigate the skin sodium content in two mouse models of MS. We additionally performed 3-T 23Na-MRI of calf skin and muscles in 29 male relapsing-remitting MS (RRMS) patients and 29 matched healthy controls. Demographic and clinical information was collected from interviews, and disease activity was assessed by expanded disability status scale scoring. 23Na-MRI and chemical analysis demonstrated a significantly increased sodium content in the skin during experimental autoimmune encephalomyelitis independent of active immunization. In male patients with RRMS, 23Na-MRI demonstrated a higher sodium signal in the area of the skin compared to age- and biological sex-matched healthy controls with higher sodium, predicting future disease activity in cranial MRI. In both studies, the sodium enrichment was specific to the skin, as we found no alterations of sodium signals in the muscle or other tissues. Our data add to the recently identified importance of the skin as a storage compartment of sodium and may further represent an important organ for future investigations on salt as a proinflammatory agent driving autoimmune neuroinflammation such as that in MS.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Skin; Sodium magnetic resonance imaging

Skin sodium measured with ²³Na MRI at 7.0 T - Linz, Peter; Santoro, Davide; Renz, Wolfgang; Rieger, Jan; Ruehle, Anjuli; Ruff, Jan; Deimling, Michael; Rakova, Natalia; Muller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Niendorf, Thoralf (NMR in Biomedicine, 2015)
Skin sodium (Na(+) ) storage, as a physiologically important regulatory mechanism for blood pressure, volume regulation and, indeed, survival, has recently been rediscovered. This has prompted the development of MRI methods to assess Na(+) storage in humans ((23) Na MRI) at 3.0 T. This work examines the feasibility of high in-plane spatial resolution (23) Na MRI in skin at 7.0 T. A two-channel transceiver radiofrequency (RF) coil array tailored for skin MRI at 7.0 T (f = 78.5 MHz) is proposed. Specific absorption rate (SAR) simulations and a thorough assessment of RF power deposition were performed to meet the safety requirements. Human skin was examined in an in vivo feasibility study using two-dimensional gradient echo imaging. Normal male adult volunteers (n = 17; mean ± standard deviation, 46 ± 18 years; range, 20-79 years) were investigated. Transverse slices of the calf were imaged with (23) Na MRI using a high in-plane resolution of 0.9 × 0.9 mm(2) . Skin Na(+) content was determined using external agarose standards covering a physiological range of Na(+) concentrations. To assess the intra-subject reproducibility, each volunteer was examined three to five times with each session including a 5-min walk and repositioning/preparation of the subject. The age dependence of skin Na(+) content was investigated. The (23) Na RF coil provides improved sensitivity within a range of 1 cm from its surface versus a volume RF coil which facilitates high in-plane spatial resolution imaging of human skin. Intra-subject variability of human skin Na(+) content in the volunteer population was <10.3%. An age-dependent increase in skin Na(+) content was observed (r = 0.78). The assignment of Na(+) stores with (23) Na MRI techniques could be improved at 7.0 T compared with current 3.0 T technology. The benefits of such improvements may have the potential to aid basic research and clinical applications designed to unlock questions regarding the Na(+) balance and Na(+) storage function of skin.
EVALuna2:3754

Sodium Accumulates in the Skin of Psoriasis Patients and in Mice with Psoriasis-Like Skin Disease - Marko, Lajos; Wild, Johannes; Rakova, Natalia; Balogh, Andras; Opitz, Elisa; Linz, Peter; Birukov, Anna; Wilck, Nicola; Dechend, Ralf; Titze, Jens; Kleinewietfeld, Markus; Krause, Andreas; et al. (BASIC & CLINICAL PHARMACOLOGY & TOXICOLOGY, 2020)
CRIS-Team WoS Importer:2020-02-07

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

Tissue sodium concentration correlates with hypertrophic vascular remodelling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susan; Harazny, Jeremy; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue Sodium Content and Arterial Hypertension in Obese Adolescents - Roth, Sophie; Marko, Lajos; Birukov, Anna; Hennemuth, Anja; Kuehnen, Peter; Jones, Alexander; Ghorbani, Niky; Linz, Peter; Mueller, Dominik N.; Wiegand, Susanna; Berger, Felix; Kuehne, Titus; et al. (Journal of Clinical Medicine, 2019)
Early-onset obesity is known to culminate in type 2 diabetes, arterial hypertension and subsequent cardiovascular disease. The role of sodium (Na+) homeostasis in this process is incompletely understood, yet correlations between Na+ accumulation and hypertension have been observed in adults. We aimed to investigate these associations in adolescents. A cohort of 32 adolescents (13-17 years), comprising 20 obese patients, of whom 11 were hypertensive, as well as 12 age-matched controls, underwent Na-23-MRI of the left lower leg with a standard clinical 3T scanner. Median triceps surae muscle Na+ content in hypertensive obese (11.95 mmol/L [interquartile range 11.62-13.66]) was significantly lower than in normotensive obese (13.63 mmol/L [12.97-17.64]; p = 0.043) or controls (15.37 mmol/L [14.12-16.08]; p = 0.012). No significant differences were found between normotensive obese and controls. Skin Na+ content in hypertensive obese (13.33 mmol/L [11.53-14.22] did not differ to normotensive obese (14.12 mmol/L [13.15-15.83]) or controls (11.48 mmol/L [10.48-12.80]), whereas normotensive obese had higher values compared to controls (p = 0.004). Arterial hypertension in obese adolescents is associated with low muscle Na+ content. These findings suggest an early dysregulation of Na+ homeostasis in cardiometabolic disease. Further research is needed to determine whether this association is causal and how it evolves in the transition to adulthood.
CRIS-Team WoS Importer:2020-01-28

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in patients with type 2 diabetes mellitus - Kannenkeril, Dennis; Karg, Marina V.; Bosch, Agnes; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2019)
Background: Tissue sodium content by 23 Na magnetic resonance imaging (MRI)has been found to be increased in arterial hypertension. We analyzed whether tissue sodium content is increased in patients with type-2 diabetes (T2DM). Methods: Patients with T2DM were compared to those with primary hypertension. Patients with T2DM were off any antidiabetic and hypertensive patients off any antihypertensive therapy for at least 4 weeks. Skin and muscle sodium content was assessed non-invasively with a 3.0 T clinical MRI system (Magnetom Verio, Siemens Health Care, Erlangen, Germany)in each patient. Results: In patients with T2DM (N = 59)we observed significantly greater muscle sodium content (diabetes: 20.6 ± 3.5 vs hypertension: 16.3 ± 2.5 mmol/l, p < 0.001)and skin sodium content (diabetes: 24.5 ± 7.2 vs hypertension: 20.6 ± 5.7 mmol/l, p = 0.01)than in those with primary hypertension (N = 33). When potential confounders (age, body mass index, gender, systolic and diastolic blood pressure, estimated glomerular filtration rate)were entered in a covariance analysis, both skin sodium content (p = 0.037)and muscle sodium content (p < 0.001)were still clearly elevated. Conclusion: Patients with T2DM have greater skin and muscle sodium content. These are the first known data to demonstrate increased tissue sodium content in patients with T2DM, measured by 23 Na magnetic resonance imaging. Since tissue sodium content is related to organ damage, therapeutic intervention should aim at reducing tissue sodium content.
CRIS-Team Scopus Importer:2019-05-21
Keywords: 23Na-MRI; T2DM; Tissue sodium content; Salt; Sodium retention

Tolvaptan treatment in an adult Fontan patient with protein-losing enteropathy: a serial 23Na-MRI investigation - Moosmann, Julia; Toka, Okan; Linz, Peter; Dahlmann, Anke; Nagel, Armin M.; Schiffer, Mario; Uder, Michael; Cesnjevar, Robert; Dittrich, Sven; Kopp, Christoph (Therapeutic Advances in Chronic Disease, 2021)
Background: Protein-losing enteropathy (PLE) is a severe complication of the univentricular Fontan circulation and associated with disturbances in salt and water homeostasis. Fontan patients with PLE have a poor prognosis, with increased morbidity and mortality. Due to limited therapeutic strategies, patients are often treated only symptomatically. Methods: We report our first experience of Tolvaptan (TLV) treatment in a Fontan patient with PLE, severe volume retention and hyponatraemia, refractory to conventional diuretic therapy. In addition to clinical parameters, we monitored drug effects including tissue sodium and volume status via serial 23Na-magnetic resonance imaging (23Na-MRI) and bioimpedance spectroscopy compared with age-matched controls. Results: 23Na-MRI identified elevated tissue sodium, which decreased under TLV treatment, as well as volume status, while serum sodium increased and the patient’s symptoms improved. During long-term treatment, we were able to differentiate between sodium and volume status in our patient, suggesting that TLV uncoupled body sodium from water. Conclusion: TLV in addition to loop diuretics improved clinical symptoms of PLE and lowered tissue sodium overload. Long-term effects should be further evaluated in Fontan patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Congenital heart disease; Fontan; RAAS; Tolvaptan

Water Conservation Overrides Osmotic Diuresis During SGLT2 Inhibition in Patients With Heart Failure - Marton, Adriana; Saffari, Seyed Ehsan; Rauh, Manfred; Sun, Ruo Ning; Nagel, Armin Michael; Linz, Peter; Lim, Tzy Tiing; Takase-Minegishi, Kaoru; Pajarillaga, Anastacia; Saw, Sharon; Morisawa, Norihiko; Yam, Wan Keat; et al. (Journal of the American College of Cardiology, 2024)
Background: Sodium-glucose cotransporter 2 inhibitors are believed to improve cardiac outcomes due to their osmotic diuretic potential. Objectives: The goal of this study was to test the hypothesis that vasopressin-driven urine concentration overrides the osmotic diuretic effect of glucosuria induced by dapagliflozin treatment. Methods: DAPA-Shuttle1 (Hepato-renal Regulation of Water Conservation in Heart Failure Patients With SGLT-2 Inhibitor Treatment) was a single-center, double-blind, randomized, placebo-controlled trial, in which patients with chronic heart failure NYHA functional classes I/II and reduced ejection fraction were randomly assigned to receive dapagliflozin 10 mg daily or placebo (1:1) for 4 weeks. The primary endpoint was change from baseline in urine osmolyte concentration. Secondary endpoints included changes in copeptin levels and solute free water clearance. Results: Thirty-three randomized, sodium-glucose cotransporter 2 inhibitor–naïve participants completed the study, 29 of whom (placebo: n = 14; dapagliflozin: n = 15) provided accurate 24-hour urine collections (mean age 59 ± 14 years; left ventricular ejection fraction 31% ± 9%). Dapagliflozin treatment led to an isolated increase in urine glucose excretion by 3.3 mmol/kg/d (95% CI: 2.51–4.04; P < 0.0001) within 48 hours (early) which persisted after 4 weeks (late; 2.7 mmol/kg/d [95% CI: 1.98–3.51]; P < 0.0001). Dapagliflozin treatment increased serum copeptin early (5.5 pmol/L [95% CI: 0.45-10.5]; P < 0.05) and late (7.8 pmol/L [95% CI: 2.77–12.81]; P < 0.01), leading to proportional reductions in free water clearance (early: −9.1 mL/kg/d [95% CI: −14 to −4.12; P < 0.001]; late: −11.0 mL/kg/d [95% CI: −15.94 to −6.07; P < 0.0001]) and elevated urine concentrations (late: 134 mmol/L [95% CI: 39.28–229.12]; P < 0.01). Therefore, urine volume did not significantly increase with dapagliflozin (mean difference early: 2.8 mL/kg/d [95% CI: −1.97 to 7.48; P = 0.25]; mean difference late: 0.9 mL/kg/d [95% CI: −3.83 to 5.62]; P = 0.70). Conclusions: Physiological-adaptive water conservation eliminated the expected osmotic diuretic potential of dapagliflozin and thereby prevented a glucose-driven increase in urine volume of approximately 10 mL/kg/d · 75 kg = 750 mL/kg/d. (Hepato-renal Regulation of Water Conservation in Heart Failure Patients With SGLT-2 Inhibitor Treatment [DAPA-Shuttle1]; NCT04080518).
CRIS-Team Scopus Importer:2024-04-12
Keywords: aestivation; decongestion; longevity; water conservation

Whole-brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Dörfler, Arnd; Uder, Michael; Zaiß, Moritz; et al. (Magnetic Resonance in Medicine, 2021)
Purpose: To enable whole-brain quantitative CEST MRI at ultra-high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online-customized (FOCUS) parallel transmission (pTx) excitation pulses and (Formula presented.) correction to achieve homogenous whole-brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good (Formula presented.) correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using (Formula presented.) correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter-subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single-point (Formula presented.) correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single-point (Formula presented.) correction can be used to achieve quantitative CEST measurements at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced as additional scans required for (Formula presented.) correction can be omitted.
CRIS-Team Scopus Importer:2021-03-12
Keywords: 7T; chemical exchange saturation transfer; fast-online customized pulses; multiple interleaved mode saturation; parallel transmission; spiral non-selective trajectory